Analog beamforming for full-duplex millimeter wave communication - R. López-Valcarce; Nuria González-Prelcic (16th International Symposium on Wireless Communication Systems (ISWCS), 2019)
Full-duplex (FD) communication has the potential for significant improvements in spectral efficiency, as long as the problem of self-interference (SI) can be overcome. For millimeter wave (mmWave) systems with large antenna arrays, beamforming based SI mitigation is attractive because of the large number of degrees of freedom available. Previously proposed precoder-combiner designs, however, suffer from a large performance loss under the hardware-constrained architectures required for operation at mmWave. In this context, we develop a new algorithm for the design of constant-amplitude analog precoders and combiners of an FD mmWave single-stream bidirectional link, significantly reducing the aforementioned performance loss.
Keywords: full-duplex; mmWave; winter